THE EFFECT OF SCAVENGER HUNT GAME TOWARDS STUDENTS' VOCABULARY MASTERY OF THE FOURTH GRADE AT SDN 4 MUARA BELITI - Endar Pradesta (LP3MKIL, 2026)
This study aims to assess the completeness of learning outcomes related to the effectiveness of the Scavenger Hunt Game method in enhancing students' vocabulary skills at SDN 4 Muara Beliti. A pre-experimental approach was employed, utilizing a one-group pre-test and post-test design, with a sample of 20 fourth-grade students. The sampling technique adopted was purposive sampling. The analysis technique used a normality test, while the hypothesis was tested with a paired sample t-test. The pre-test showed an average score of 41.50 with a standard deviation of 17.021, with only 2 students reaching the